MCTS : Windows server virtualization configuration study guide (exam 70-652) - Panek, William, 1970- (Serious skills., 2009)
The MCTS is Windows Server Virtualization Configuring exam, and is Microsoft's newest addition to their exam repertoire and tests candidates' ability to use Hyper-V and server virtualization as part of their network infrastructure solution. The exam targets IT professionals who are looking to enhance their skills and distinguish themselves from the rest of the pack. This guide reviews the tasks that are mandatory for candidates to know: installing Hyper-V, configuring and optimizing Hyper-V, deploying virtual machines, and managing and monitoring virtual machines. The CD-ROM contains coverage.